Desain, Manufaktur dan Uji Kinerja Mesin Pengolah Serbuk Jahe Merah - Mirza Yusuf; Ferriawan Yudhanto; Dimas Pulung Purbajati (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
Design of the red ginger powder production machine aims to increase UMKM(Usaha Mikro Kecil dan Menengah) in the Yogyakarta area. By making a semiautomatic red ginger powder machine, it can increase production capacity and improve the economy for UMKM. Component design is divided into 3 processes, namely; designing the frame, designing the stirring shaft, and designing the cooking tank. There are first adjusted to the design that has been made using the solid works software which is then applied by assembling other components. The drive system on the powdered red ginger production machine uses an AC electric motor which is then forwarded into the v-belt transmission then the output from the transmission is forwarded to the stirring shaft.